2021
DOI: 10.3390/universe7060203
|View full text |Cite
|
Sign up to set email alerts
|

Transport Coefficients of Hyperonic Neutron Star Cores

Abstract: We consider transport properties of the hypernuclear matter in neutron star cores. In particular, we calculate the thermal conductivity, the shear viscosity, and the momentum transfer rates for npΣ−Λeμ composition of dense matter in β–equilibrium for baryon number densities in the range 0.1–1 fm−3. The calculations are based on baryon interactions treated within the framework of the non-relativistic Brueckner-Hartree-Fock theory. Bare nucleon-nucleon (NN) interactions are described by the Argonne v18 phenomeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(159 reference statements)
0
6
0
Order By: Relevance
“…Transport coefficients for the hypernuclear NS cores can be in principle, calculated using the similar formalism as studied here. For the nonmagnetized case this was done by [100] for two models of hypernuclear interaction. The momentum transfer rates within the free-particle model and npeΣ − composition were considered in [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transport coefficients for the hypernuclear NS cores can be in principle, calculated using the similar formalism as studied here. For the nonmagnetized case this was done by [100] for two models of hypernuclear interaction. The momentum transfer rates within the free-particle model and npeΣ − composition were considered in [9].…”
Section: Discussionmentioning
confidence: 99%
“…When collisions of charged baryons are considered, in principle the interference between the electromagnetic and strong interaction channels needs to be taken into account [98]. However, it was found that the charged baryons usually give negligible contribution to the transport coefficients [83,99,89,100]. Therefore, we neglect the interference contribution and consider the electromagnetic and strong channels separately for simplicity.…”
Section: Microphysics Of Quasiparticle Collisions In Ns Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, a final remark about the transport coefficients of hyperonic matter. In this sector, few calculations have been completed [267]. These calculations are relevant for the very important application in astrophysical systems, like BNSM and SNe.…”
Section: Possible Signatures Of the Presence Of Hyperons In Astrophysical Dynamical Systemsmentioning
confidence: 99%
“…A microscopic study of thermal conductivity and shear viscosity of hyperonic matter have been very recently proposed in Ref. [267], in the framework of BHF approaches using versions a and e of the NSC97 NY and YY interactions. The effect of hyperonic three-body forces was not included.…”
Section: Possible Signatures Of the Presence Of Hyperons In Astrophysical Dynamical Systemsmentioning
confidence: 99%